Основні проблеми працевлаштування молоді у системі споживчої кооперації України - Шевченко, О. О.; Shevchenko, О. (КНТУ, 2013)
У статті розглядаються основні проблеми працевлаштування випускників вищих навчальних закладів у системі споживчої кооперації України. Показано недоліки молодіжної кадрової політики на законодавчому та внутрішньо управлінському рівні. The aim of the article is to identify the main problems and peculiarities of hiring young professionals in the system of consumer cooperatives in Ukraine. Analysed the fundamental laws that govern the process of youth employment. Described the main shortcomings of youth personnel policy on legislation and on internal management level. Defined the main stages of staffing in the enterprises and organizations of consumer cooperatives in Ukraine. Found that these stages are imperfect and contradict to the modem methods of personnel management. Indicated that system of consumer cooperatives in Ukraine there are no clear distinctions between stages attract young professionals and specialists with work experience. Thus, the major problems of youth in the system of personnel policies Consumer Cooperatives in Ukraine are: inadequate legal framework, lack of proper enforcement of regulations; outdated theoretical and methodological approaches to staffing in companies and organizations of consumer cooperatives Ukraine. Prospects for further research in this area are: finding ways to improve the selection of personnel for enterprises Consumer Cooperatives in Ukraine; developing a mechanism for recruitment of young professionals to cooperative enterprises; and searching ways of informing graduates and managers about the prospects for their cooperation.
The main problems of youth employment in the system of consumer cooperatives in Ukraine
Keywords: молодіжна кадрова політика; молодий спеціаліст; комплектація персоналу; споживча кооперація; staff policy for young specialist; young specialist; recruitment; consumer's cooperative society